Seleção de jabuticabeiras juvenis considerando o vigor, o potencial antioxidante e a tolerância a geadas - Radaelli, Juliana Cristina (2016)
The jabuticaba tree has great potential for commercial exploitation. However, its is very little used. This fact shows to be necessary to do studies that allow understand their growth behavior during the year and, if it is tolerant to frost. So that it can establish management strategies for cultivation in orchard. Other point, it is the fact that the long juvenile period of jabuticaba tree limits its use. However, many species have compound leaves that characterize them as functional compounds, what to posible its commercialization. If the leaf jabuticaba tree also present such nutraceutical compounds, this it may become an alternative source of income until the plant to start its yield. The objectives of this study were to analyze the growth behavior, the occurrence of flowering and fruit set, and the frost tolerance of jabuticaba tree genotypes present in the collection of Native Fruit from UTFPR – Câmpus Dois Vizinhos. Associated growth analysis was made evaluation of genetic divergence among these genotypes, checking the adaptive behavior in orchard condition through adaptability and stability analysis based on growth measures to stem and shoots; estimating the repeatability coefficient of stem length of characters and primary shoots, and determine the minimum number of evaluations able to provide certain levels of prediction of the actual value of these individuals. Also determined the genetic divergence among genotypes as the leaves of antioxidant activity by DPPH and ABTS methods, as well as the determination of total phenolics. The genotypes studied were put in orchard in 2009. The growth response in the three cycles was variable between months and genotypes, what it can be difficult the practices in the orchard if it do not use clones. Genotypes 'Silvestre' and 'Açú' showed greater width and leaf area compared with other genotypes, but such behavior is not favored for increased stem growth and primary shoots. Foliar increments in most genotypes occurred in the fall for leaf width, spring for length and leaf area, despite the winter also arise with genotypes, it showed superiority to width and leaf area. Most jabuticabas trees were juvenile stage with only four starting at its transition between the vegetative and reproductive phase. Tolerance to frost was observed in 26 families jabuticabeira of the 29 present in the collection. The diversity among the genotypes was to change with the time, already in each cycle, there was the formation of different groups by the methods used. The methods tested for adaptability and stability of the jabuticaba tree growth behavior did not show the same pattern in the results. The number of measurements needed to predict the actual value of genotypes based on variables evaluated was approximately one to the stem length and four for the shoots based on the method of main components of covariance with 90% probability. he antioxidant activity of the extracts of leaves of jabuticaba tree genotypes were demonstrated high when compared to other species by methods DPPH and ABTS, as well as the amount of phenolic compounds. Genotype 'Silvestre' and 'IAPAR' showed the highest antioxidant activity in the leaves. However, the genetic divergence among genotypes jabuticaba tree from collection of Native Fruit trees at UTFPR - Câmpus Dois Vizinhos for antioxidant activity leaves showed that they have great homogeneity among them and the low divergence. However, it is recommended as possible hybridization the use as parents, José 4, IAPAR 4 and Fernando Xavier genotypes.